Arthroscopic management of posterior shoulder instability: Diagnosis, indications, and technique - Bradley, J. P.; Forsythe, B.; Mascarenhas, R. (Clinics in Sports Medicine, 2008)
With increased understanding of the different patterns of posterior shoulder instability, diagnostic acumen and successful treatment algorithms have evolved. Improvements in imaging and advancements in arthroscopic surgical techniques have facilitated this progress. In athletic populations, recurrent posterior subluxations (RPSs) are far more common than recurrent or locked posterior dislocations. Conservative and operative management of posterior instability is individualized to meet the demands of its diverse patient population, ranging from post-traumatic instability in contact athletes to RPSs in overhead athletes.